2013
DOI: 10.1007/s00125-013-2836-x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inhibition of nitric oxide synthesis in non-diabetic individuals produces a significant deterioration in glucose tolerance by increasing insulin clearance and inhibiting insulin secretion

Abstract: Aims/hypothesis Endogenous NO inhibits insulin release in isolated beta cells and insulin-degrading enzyme activity in hepatocytes, while NO release from endothelial cells has been suggested to enhance insulin action. We assessed the overall effect of systemic inhibition of endogenous NO synthesis on glucose homeostasis in humans. Methods Twenty-four non-diabetic volunteers underwent two hyperglycaemic (+7 mmol/l) clamps with either saline or L-NGnitroarginine methyl ester (L-NAME, at rates of 2.5, 5, 10 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…The results by Natali et al [1] also explain the previously reported association between the endogenous NO synthesis inhibitor asymmetric dimethylarginine (ADMA) and the risk of future deterioration of glucose tolerance [5,6]. Following the report of this association by Mittermayer et al [5] in 77 women with previous gestational diabetes, we have identified the same relationship in 80 non-diabetic men with stable angina who were followed for a 4.5 year period [6].…”
Section: Admasupporting
confidence: 77%
See 4 more Smart Citations
“…The results by Natali et al [1] also explain the previously reported association between the endogenous NO synthesis inhibitor asymmetric dimethylarginine (ADMA) and the risk of future deterioration of glucose tolerance [5,6]. Following the report of this association by Mittermayer et al [5] in 77 women with previous gestational diabetes, we have identified the same relationship in 80 non-diabetic men with stable angina who were followed for a 4.5 year period [6].…”
Section: Admasupporting
confidence: 77%
“…Moreover, in both reports ADMA and HOMA-IR were unrelated [5,6]. Thus, on the basis of the findings by Natali et al [1], the predictive ability of ADMA in these studies [5,6] might hypothetically be attributable not to concomitant IR but possibly to accompanying relative insulin deficiency, inasmuch as the long-term effects of ADMA are similar to those of shortterm NO inhibition. Nevertheless, this concept is challenged by the recent concerns raised by Reaven [7] with regard to using HOMA-IR as an index of IR when altered insulin clearance is the major determinant of the change in fasting insulinaemia.…”
Section: Admamentioning
confidence: 51%
See 3 more Smart Citations